1997
DOI: 10.1080/01688639708403745
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary profile of neuropsychological deficits associated with major depression

Abstract: A profile of neuropsychological deficits of clinically depressed (major depression) but otherwise unimpaired individuals is presented, based on a meta-analysis of all studies published since 1975 and meeting stringent methodological and sample selection criteria. Deficits are discussed separately for different cognitive areas in terms of mean size of deficit, variability between studies, variability of individual scores in depressed populations relative to that of controls, and expected proportion of depressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
270
9
9

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 444 publications
(315 citation statements)
references
References 52 publications
27
270
9
9
Order By: Relevance
“…In addition, the findings of the lesion study by Shammi and Stuss (1999) suggested a contribution of the PFC to humor processing. The observed humor processing deficits in the present investigation may thus be linked to PFC dysfunction in major depression, as shown by recent studies (Veiel, 1997).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In addition, the findings of the lesion study by Shammi and Stuss (1999) suggested a contribution of the PFC to humor processing. The observed humor processing deficits in the present investigation may thus be linked to PFC dysfunction in major depression, as shown by recent studies (Veiel, 1997).…”
Section: Discussionsupporting
confidence: 85%
“…Major depression is associated with cognitive deficits including memory and executive impairment (Veiel, 1997;Zakzanis et al, 1998). These in turn have been linked to dysfunction of fronto-subcortical networks including the dorsolateral prefrontal cortex (DLPFC), the ventrolateral prefrontal cortex (VLPFC), the anterior cingulate cortex (ACC), the basal ganglia and the hippocampus (Brody et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The DAN network shows increased synchronization during goal-directed processes (Corbetta et al, 1998;Kim, 2010), and MDD is characterized by poor performance in cognitive control tasks (Veiel, 1997;Zakzanis et al, 1998) as well as dysfunction in dorsolateral and ventrolateral prefrontal cortex and anterior cingulate cortex during cognitive control tasks (Brody et al, 2001;Rogers et al, 2004). MDD is also characterized by altered orbital frontal cortex activation in the context of processing rewards Smoski et al, 2009), anticipating rewards , and while processing sad distracting information (Elliott et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis, Veiel (1997) found the largest differences between depressed patients and healthy controls on set shifting and inhibition tasks. In addition, planning and working memory impairments have been frequently observed in major depression (see DeBattista, 2005).…”
Section: Introductionmentioning
confidence: 99%